Evaluation of the effectiveness of 3D vascular stereoscopic models in anatomy instruction for first year medical students. Issue 1 (6th June 2016) - Cui, Dongmei; Wilson, Timothy D.; Rockhold, Robin W.; Lehman, Michael N.; Lynch, James C.
Abstract : The head and neck region is one of the most complex areas featured in the medical gross anatomy curriculum. The effectiveness of using three‐dimensional (3D) models to teach anatomy is a topic of much discussion in medical education research. However, the use of 3D stereoscopic models of the head and neck circulation in anatomy education has not been previously studied in detail. This study investigated whether 3D stereoscopic models created from computed tomographic angiography (CTA) data were efficacious teaching tools for the head and neck vascular anatomy. The test subjects were first year medical students at the University of Mississippi Medical Center. The assessment tools included: anatomy knowledge tests (prelearning session knowledge test and postlearning session knowledge test), mental rotation tests (spatial ability; presession MRT and postsession MRT), and a satisfaction survey. Results were analyzed using a Wilcoxon rank‐sum test and linear regression analysis. A total of 39 first year medical students participated in the study. The results indicated that all students who were exposed to the stereoscopic 3D vascular models in 3D learning sessions increased their ability to correctly identify the head and neck vascular anatomy. Most importantly, for students with low‐spatial ability, 3D learning sessions improved postsession knowledge scores to a level comparable to that demonstrated by students with high‐spatial ability indicating that the use of 3D stereoscopic models may be particularly valuable to these students with low‐spatial ability. Anat Sci Educ 10: 34–45. © 2016 American Association of Anatomists.